2000
DOI: 10.1111/j.1572-0241.2000.01862.x
|View full text |Cite
|
Sign up to set email alerts
|

Mean corpuscular volume may be a useful index of risk for colorectal adenoma in middle-aged Japanese men

Abstract: A high MCV value may be used as a simple index of the risk of colorectal adenomas, regardless of alcohol consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
1
4
1
Order By: Relevance
“…44 NSAIDs inhibit CRA progression through inflammatory factors. 45,46 Compared with research describing western populations that has shown significant associations between CRA occurrence and alcohol and cigarette consumption, [39][40][41]47 the current nonsignificant findings in a Chinese population might be the result of differences in alcohol and cigarette consumption compared with other populations. In the present study, the protective factors for CRA recurrence during follow-up were the same as for CRA occurrence (i.e.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…44 NSAIDs inhibit CRA progression through inflammatory factors. 45,46 Compared with research describing western populations that has shown significant associations between CRA occurrence and alcohol and cigarette consumption, [39][40][41]47 the current nonsignificant findings in a Chinese population might be the result of differences in alcohol and cigarette consumption compared with other populations. In the present study, the protective factors for CRA recurrence during follow-up were the same as for CRA occurrence (i.e.…”
Section: Discussioncontrasting
confidence: 58%
“…Alcohol is a known folate inhibitor that affects dietary methyl supply and therefore is associated with CRA and CRC. 39 41 In the present study, some factors were independent risk factors of CRA occurrence (age, BMI and family history of colorectal diseases), and two were independent protective factors (folic acid and a history of gastroenterology drug use). Visceral fat obesity has been confirmed as an independent risk factor for CRA, 42 which has been suggested to bring about its affects by increasing insulin-like growth factor 1, leading to the stimulation of colorectal epithelium proliferation.…”
Section: Discussionsupporting
confidence: 49%
“…As a measure of the average volume of a red blood cell, mean corpuscular volume (MCV) was related to the prognosis of liver cancer ( 7 ), esophageal cancer ( 8 ) and adenocarcinomas of the gastroesophageal junction ( 9 ). Interestingly enough, MCV was also reported to be associated with the risk of colorectal adenoma ( 10 ), advanced CRC ( 11 ) and response to chemotherapy in CRC ( 12 , 13 ), suggesting MCV had the potential to be an ideal biomarker and be put into clinical application. In particular, previous study revealed that high MCV value may be used as an index of the risk of colorectal adenomas ( 10 ), but a recent research reported decreased MCV was an independent predictor for the detection of advanced colorectal cancer ( 11 ), indicating that the clinical role of MCV in colorectal cancer was still uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…(mutation) (8-10), APC Mut. (11)(12)(13)(14), CRP (15)(16)(17)(18), CEA (18-23), CA 19-9 (18,22,24), WBC (25), MCV (26)(27)(28)(29), and mutation numbers in related genes were analyzed. In our study, 6384 patient data obtained from 22 articles were used.…”
Section: Resultsmentioning
confidence: 99%